Possibility of using a lithotrophic iron-oxidizing microbial fuel cell as a biosensor for detecting iron and manganese in water samples - Phuong Hoang Nguyen Tran; Tha Thanh Thi Luong; Thuy Thu Thi Nguyen; Huy Quang Nguyen; Hop Van Duong; Byung Hong Kim; Hai The Pham (ROYAL SOC CHEMISTRY, 2015)
Iron-oxidizing bacterial consortia can be enriched inmicrobial fuel cells (MFCs) operated with ferrous iron as the sole electron donor. In this study, we investigated the possibility of using such lithotrophic iron-oxidizing MFC (LIO-MFC) systems as biosensors to monitor iron and manganese in water samples. When operated with anolytes containing only ferrous iron as the sole electron donor, the experimented LIO-MFCs generated electrical currents in response to the presence of Fe2+ in the anolytes. For the concentrations of Fe2+ in the range of 3-20 mM, a linear correlation between the current and the concentration of Fe2+ could be achieved (r(2) = 0.98). The LIO-MFCs also responded to the presence of Mn2+ in the anolytes but only when the Mn2+ concentration was less than 3 mM. The presence of other metal ions such as Ni2+ or Pb2+ in the anolytes reduced the Fe2+-associated electricity generation of the LIO-MFCs at various levels. Organic compounds, when present at a non-excessive level together with Fe2+ in the anolytes, did not affect the generation of electricity, although the compounds might serve as alternative electron donors for the anode bacteria. The performance of the LIO-MFCs was also affected to different degrees by operational parameters, including surrounding temperature, pH of the sample, buffer strength and external resistance. The results proved the potential of LIO-MFCs as biosensors sensing Fe2+ in water samples with a significant specificity. However, the operation of the system should be in compliance with an optimal procedure to ensure reliable performance.